Dancing with wolves: how R&D human capital can benefit from coopetition. (1st June 2021) - Vlaisavljevic, Vesna; Gopalakrishnan, Shanthi; Zhang, Haisu; Cabello‐Medina, Carmen; Guilbault, Melodi
Abstract : This research examines the impact of coopetition (i.e., competitor alliances) on the development of internal R&D human capital. The study was conducted using survey data from 111 biotech firms in Spain and United States. Results show a mediation relationship: coopetition increases a firm's internal R&D human capital via its proactiveness to pursue R&D partnerships. To further examine the link between competitor alliances and R&D partnerships, we also investigate the role of two moderators, alliance satisfaction and alliance coordination. We argue that the two factors exert opposite moderation effects on the relationship between coopetition and proactiveness to pursue R&D partnerships. Results demonstrate that when a firm and its alliance partners are satisfied with each other, the effect of coopetition on proactiveness decreases, but the moderation effect of alliance coordination, though predicted to be in the opposite direction, is not significant.